AL-IJARAH: UNDERSTANDING, LEGAL BASIS AND PROBLEMS OF CONTEMPORARY PRACTICES IN SHARIA BUSINESS - Munadi Munadi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
The purpose of this study is to discuss the concept of al-Ijarah or leasing which is one of the legal contracts or transactions in the world of Islamic banking. When the concept of al-Ijarah is applied in contemporary Sharia business, there are several problems in its application that require solutions in its study. This research is a research with a qualitative descriptive approach using some literature related to the discussion (Libarary Research). After going through some of the literature, it was discussed and analyzed. The conclusions in this study include: Ijarah is a form of transaction in Islamic law which essentially is the existence of two parties who agree to rent out goods or services (labor and or professionalism) with certain rewards. As for the texts that underlie it is QS. 65:6, some hadiths of the Prophet Muhammad and the consensus of the fuqaha. An accountable transaction, Ijarah is completed with the terms and pillars as a measuring tool for whether the transaction is valid, familial or void. The conditions are: The willingness of both parties, the benefits of the object of Ijarah are known with certainty, the leased item has certain specifications, the object for rent is something permissible, can be handed over, not an obligation and wages are something of value. The pillars are: Two parties to the transaction, transaction editor, benefits and wages. The character of the Ijarah transaction is binding on the parties who have made the transaction agreement. The variety is rental, lease purchase and labor. An Ijarah transaction can end when the goal or deadline has been achieved, the default of one of the parties or the death of one of the parties.